WARISAN TASAWUF AKHLAQI SYEKH SHOLEH DARAT DAN SYEKH IHSAN JAMPES: WARISAN TASAWUF AKHLAQI SYEKH SHOLEH DARAT DAN SYEKH IHSAN JAMPES - khotimah, khusnul; Mu’tamar; Djamil, Abdul; Nurcholis, Nanang (EDUCATIVA, 2023)
One of the legacies of the Indonesian scholars is akhlaqi tasawuf. Since Walisongo, Sufism has permeated and colored the spread of Islam in the archipelago. From various works left by the Indonesian scholars from generation to generation, the spirit of akhlaqi tasawuf was passed down from generation to generation. The work of Syekh Sholeh Darat and Syekh Ihsan Jampes can explain how this tasawuf dialogue with the local community so that it can be easily carried out. By tracing this akhlaqi tasawuf, it will be an entry point to mapping the genealogy of thought, the historical basis and the epistemological formula in recognizing religious national identity, particularly in relation to morality. This is important, because so far the national identity has been getting away from the values ​​that have been ingrained in the archipelago. In this paper, it is emphasized that the Islamic tradition in Indonesia has become one of the shapers and pillars of today's national identity. This tradition has left various socio-cultural legacies that need to be tracked and found, especially the transmission paths of Islam's entry into the archipelago. This socio-cultural heritage has become one of the foundations of the massively constructed identity/identity of the Indonesian nation, which later became the foundation of Indonesian Islam today, namely tolerance, moderation, peace and openness. The heritage of the Indonesian Ulama also influences the extent to which the relations and interactions of the Ulama form a network of knowledge, knowledge and culture which is passed on to the following generations. There are two figures and works or manuscripts that are the focus of this paper, namely Sheikh Sholeh Darat Semarang and Sheikh Ihsan Jampes, who have brought an understanding of Sufism akhlaqi al Ghazali in strengthening Indonesian national identity on the basis of manners and politeness.